COVID-19 vaccine hesitancy in Riley County, Kansas - Mason, Lindsay (My University, 2022)
My applied practical experience dealt with the complex and challenging issue of COVID-19 vaccine hesitancy within Riley County, Kansas. Through my APE I was able to gain experience working with the Riley County Health Department by attending testing and vaccination events and helping to organize hundreds of patient files. My experience resulted in the creation of several social media outreach posts, three blog entries, and a vaccine hesitancy survey. Members of the Riley County Health Department and I distributed a survey to local Riley County employers to gain views and opinions regarding the COVID-19 vaccine. Survey results determined that individuals who chose not to be vaccinated believed the vaccine to be unsafe, ineffective, and unnecessary. Moreover, the majority of unvaccinated individuals reported that there was no acceptable incentive for vaccination.
Keywords: vaccine hesitancy; public health